PELATIHAN AI UNTUK MENINGKATKAN KOMPETENSI GURU PENDIDIKAN AGAMA ISLAM - Fajrin, Rara Intan Mutiara; Sukemi, Rochmawati Sholikah; Kusuma, Nanda Arief (AL HAZIQ: Journal of Community Service, 2025)
The utilization of Artificial Intelligence (AI) technology in Islamic Religious Education (PAI) learning at elementary schools remains suboptimal, especially in rural areas like SDN Gejugan and SDN Pelemrejo. This community service project aimed to improve PAI teachers’ digital competence through direct practice-based training and guidance involving university students as facilitators. The training results showed enhancement in teachers’ ability to operate AI applications and develop digital learning media. Student involvement supported the learning by doing process, accelerating teachers’ technology mastery. The main challenge faced remains the limitation of technological facilities. Continuous training and improvement of technology infrastructure are necessary to sustain effective digitization of PAI learning.